The Diffusion of Collaborative Justice: The Politics of Learning in the Development of Drug Courts. (3rd July 2019) - Mak, Maxwell; Rutledge, Jennifer Geist
Abstract: We investigate the creation of county-level drug courts in California, Florida, and New York and seek to answer the following questions: (1) what conditions are necessary for the adoption of institutional innovations by the judiciary; and (2) what conditions will encourage or deter the spread of these innovations? We find that preconditions against these alternative approaches can be overcome through the diffusion mechanism of learning and demonstrate that policy diffusion is most important when viewed as having a conditional relationship with institutional and political context. When viewed as a dynamic relationship, we also find that diffusion mechanisms do not operate only in a positive direction and, instead, can work to mitigate or amplify government opposition to changes in judicial approaches.